Enduring Struggles and Protracted War: Hatred as a Multi-Faceted Construct - Abuelaish Izzeldin; J. Yousufzai Susan; Sanchos Marcos; Oliver Amalya (Journal of Human Psychology, 2025)
This paper examines the concept of conflict- and war-related hatred as a multifaceted construct. Drawing upon various theoretical frameworks, we hypothesized that hatred in the context of conflict and war would encompass five distinct dimensions: Groupthink (Contagious Hatred), Destructiveness, Exposure, Chronicity, and Extreme-Severe Affect. To empirically validate this conceptual framework, we conducted a second-order factor analysis using data from 709 questionnaire responses collected from citizens in the Gaza Strip. The findings revealed that the optimal model comprises three primary constructs: Contagious Hatred, Chronicity, and Extreme- Severe Affect. Based on these results, we argue that collective existential threats in contexts of protracted conflict and war amplify groupthink, foster a sense of chronicity, and evoke intense negative affect. These findings underscore the complexity of hatred as a psychological and social phenomenon in conflict zones.
Keywords: Exposure